Pengaruh Penggunaan Metode Card Sort Terhadap Hasil Belajar Siswa Dalam Kegiatan Pembelajaran Sbdp Kelas III SDN 15 Gurung Kempadik - Emi; Mastiah; Kurnia Dyah Anggorowati (putrapublisher.org, 2025)
The purpose of this research is to determine the impact of the card sorting method on the learning outcomes of third-grade students at Elementary School 15 Gurung Kempadik after using this method in Arts and Crafts learning. This research is experimental, using a pre-experimental design of one group pretest-posttest. The population in this study includes all third-grade students at Elementary School 15 Gurung Kempadik, totaling 23 students, consisting of 14 male students and 9 female students. The sample used in this study is a saturated sample, where all members of the population are made as the sample. The instrument used in this research is multiple-choice questions for the pretest and posttest, totaling 14 questions. The data analysis technique used is the t-test (Wilcoxon Signed-Rank Test). The results showed a negative rank of 0.00 and a positive rank of 12.00 with a significant value (p) of 0.000 (p).